2021
DOI: 10.1111/cpr.13167
|View full text |Cite
|
Sign up to set email alerts
|

Lipid raft involvement in signal transduction in cancer cell survival, cell death and metastasis

Abstract: Lipid rafts are cholesterol‐ and sphingolipid‐enriched specialized membrane domains within the plasma membrane. Lipid rafts regulate the density and activity of signal receptors by compartmentalizing them, promoting signalling cascades that play important roles in the survival, death and metastasis of cancer cells. In this review, we emphasize the current concept initially postulated by F. Mollinedo and C. Gajate on the importance of lipid rafts in cancer survival, death and metastasis by describing representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 112 publications
(185 reference statements)
0
48
0
Order By: Relevance
“…Compared to the surrounding membrane, lipid rafts exhibit a more ordered and tightly packed structure. Lipid rafts are involved in various biological events, such as protein transport and apoptosis, because they provide a stable platform and contribute to the mediation and amplification of various cellular signals [ 29 , 30 ]. In the present study, MβCD was administered to disrupt intact lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the surrounding membrane, lipid rafts exhibit a more ordered and tightly packed structure. Lipid rafts are involved in various biological events, such as protein transport and apoptosis, because they provide a stable platform and contribute to the mediation and amplification of various cellular signals [ 29 , 30 ]. In the present study, MβCD was administered to disrupt intact lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be possible to reverse the status of the immune desert by targeting B3GALT4 in NB cells. Lipid rafts, plasma membrane microdomains enriched in gangliosides, play a significant role in regulating signaling pathways and cancer progression [57][58][59]. Previous studies have reported that the gangliosides GD3 and GM1 are associated with lipid raft formation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid rafts are cholesterol- and sphingolipid-enriched membrane domains containing specific proteins for specialized cellular functions. Lipid rafts are involved in the signal transduction in cancer cell survival, cell death, and metastasis [ 31 ]. Alterations of lipid rafts are also linked to age-associated neurodegenerative diseases, such as Alzheimer’s disease and Parkinson’s disease [ 32 ].…”
Section: Cholesterol Homeostasismentioning
confidence: 99%